Sulforaphane Ameliorates the Severity of Psoriasis and SLE by Modulating Effector Cells and Reducing Oxidative Stress - Du, Pei; Zhang, Wenqian; Cui, Haobo; He, Wei; Lu, Shuang; Jia, Sujie; Zhao, Ming (Frontiers in Pharmacology, 2022)
Background: Sulforaphane, which is found in cruciferous vegetables, has been reported to have anti-inflammatory, antioxidant, and antitumour activities. However, whether sulforaphane has therapeutic effects on inflammatory or autoimmune skin diseases, including psoriasis and systemic lupus erythematosus (SLE), is unclear. Methods: The therapeutic effects of sulforaphane were analyzed in Imiquimod (IMQ)-induced psoriasis-like mice and lupus-prone MRL/lpr mice. In IMQ-induced psoriasis-like mice treated with sulforaphane (55.3 and 110.6 μmol/kg) or vehicle control, the pathological phenotypes were assessed by the psoriasis area and severity index (PASI) score, haematoxylin-eosin staining (H&E) and quantifying of acanthosis and dermal inflammatory cell infiltration. The proportions of T cell subsets in draining lymph nodes (dLNs) and spleens were examined by flow cytometry. In MRL/lpr mice treated with sulforaphane (82.9 μmol/kg) or vehicle control, mortality and proteinuria were observed, and the glomerular pathology was examined by H&E staining. C3 and IgG depositions in kidney sections were examined by immunofluorescence staining. The proportions of plasma cells, follicular helper T (Tfh) cells, neutrophils and dendritic cells in the dLNs and spleens were examined by flow cytometry. Finally, we examined the Malondialdehyde (MDA) concentration by thiobarbituric acid reactive substance assay and the expression of Prdx1, Nqo1, Hmox1, and Gss by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Results: Sulforaphane ameliorated the skin lesions in IMQ-induced psoriasis-like mice and the renal damage in lupus-prone MRL/lpr mice. In IMQ-induced psoriasis-like mice, sulforaphane reduced the proportions of Th1 and Th17 cells and increased the expression of antioxidant gene Prdx1. In lupus-prone MRL/lpr mice, sulforaphane increased the lifespan and the expression of Prdx1, and decreased the proportions of plasma cells, Tfh cells, neutrophils, and dendritic cells in the dLNs and spleens and the concentration of MDA. Conclusion: Sulforaphane has significant therapeutic effects on IMQ-induced psoriasis-like mice and lupus-like MRL/Lpr mice by reducing inflammatory and autoimmune-related cells and oxidative stress. These findings provide new evidence for developing natural products to treat inflammatory and autoimmune diseases.